Microwave Cavities Generated Active Species in Plasmas - André Ricard (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Microwave plasma sources are described from low Ar gas pressure (< 1 Torr) to high gas pressures (> 10 Torr up to the atmospheric gas pressure) in N2 and Ar. At low gas pressure, the plasma diameter is over 1 cm, typically 2.6 cm and at high gas pressure, it needs discharge tubes < 1cm, down to 0.1 cm. The microwave plasmas have been studied from low to atmospheric gas pressure in rare gases (mainly Ar) and gas mixtures containing N2. At low gas pressure, it is found the surface wave plasmas, produced by patented launchers Surfatron and Surfaguide, which were developed by Michel Moisan in the Plasmas Lab. of the Montreal Univ. in 1975 [1] . At high gas pressure from a few Torr up to the atmospheric gas pressure, the SW plasmas Surfatron at low power and Surfaguide at high power are still operating. It is also given the results obtained by a resonant cavity in N2 - xO2 with x = 0-20%. It is presently reported the detection of plasma active species obtained by optical spectroscopy. The main used frequency was 2450 MHz. The plasma power could vary from a few Watts (surfatron) up to a few 103 Watts (Surfaguide, resonant cavity). The plasma can be produced in a static gas flow, mainly at low gas pressure and up to several liters per minute (slpm) at high gas pressures. The optical spectroscopy was set up first to obtain the spatial distribution of radiative species, mainly in Ar gas at low gas pressure in the perspective to characterize the SW plasmas. Then the radial distribution of Ar metastable density was obtained by resonant optical absorption. At medium (a few Torr) up to the atmospheric gas pressure, flowing HF plasmas (resonant cavity) and SW plasmas were produced in gas mixtures with N2 to produce N -atoms and other active species such as N2 metastable molecules and N2+ions which are studied inside the plasma and in afterglow conditions. It discusses the kinetics reactions relating the N2(X,v),N2(A,v’),N2(B,v’),N2(C,v’),N2+(X,v’) and N2+(B,v’) interfering in the radiative emissions of N2(B,v’),N2(C,v’) and N2+(B,v’) states. At atmospheric gas pressure, the plasmas are mainly in Ar dominant gas, easier to ionize. In these conditions, the plasmas are characterized by the electron density and the gas temperature which will be reported for specific microwave plasmas sources. Depending on plasma parameters such as powers, flow rates and exit tube diameters, the plasmas were more and less near the Local Thermodynamic Equilibrium (LTE) as demonstrated in Montreal Univ., Lisbon IST and Cordoba Univ. The conclusion was that the N2 excited states are mainly produced from the N2 ground state by electron collisions in a resonant microwave cavity. It was estimated that the LTE was nearly reached in a 100 Torr, 300-500 W N2 plasma in a quartz tube of i.d.10 mm. with equality of vibrational and rotational temperatures.